Unsettling planning In Perth: Indigenous planning in a boom - Jones, Tod; Cox, S.; Cozens, Paul (UWA Publishing, 2016)
Since English occupation of the Swan Coastal Plain in 1829 Aboriginal people in Western Australia have experienced a process of social, political, legal and spatial marginalisation (Bolton 1981; Carter 2005; Green 1984; Haebich 1992; Hunter 2012). While the most oppressive policies of cultural extermination were in place from the start of the Aborigines Act 1905 until the custodial powers of the State began to reduce in 1964, the effects of marginalisation continue to have repercussions for Aboriginal people and Western Australians. However, both Aboriginal people’s marginalisation and Perth’s economic growth did not have uniform effects and has presented both possibilities and problems. The focus of planning policies and boom-time economic opportunities flowed to some locations and groups and not others. In this chapter we unsettle Indigenous planning in Greater Metropolitan Perth (henceforth, Perth), in the context of Western Australia’s most recent resources boom, through a critical appraisal of five key areas of Indigenous planning policy: land claims; Aboriginal heritage regulations; Aboriginal participation in urban planning processes; management of important Aboriginal places; and interpretation of places.